Analisis Jumlah Lubang Injektor dan Nilai Oktan Terhadap Kinerja Motor Bensin - Santoso; Purwoko; Akbar Anugrah; Mutrofin (Politeknik Negeri Malang, 2024)
The rapid development of the automotive sector in electronic systems is accompanied by an increase in injector types that have different numbers of holes, especially on motorbikes. It is hoped that the different number of holes in the injector will have certain advantages which are expected to improve its performance. This research aims to determine the effect of using variations in the number of holes in the injector and the octane value of the fuel on petrol motor power. The research method uses experiments with descriptive analysis. The independent variable is the number of holes in the injector, 4, 6, and 8 and the octane value of the fuel is 90 and 92. In the power testing process using engine speed from 1000 rpm to 9000 rpm and the bound variable is the power. The results of this research show that there is a significant influence with the greatest power on the type of injector with 4 holes and fuel with an octane value (RON) of 92, namely 6.072 [kW] at an engine speed of 6500 [rpm]. When using fuel with an octane rating (RON) of 90, the greatest power in the injector type with 6 holes is 5,451 [kW] at an engine speed of 7000 [rpm]. In general, all types of injectors can be used, because the difference in power produced is not too large.